Internet of Things (IoT) as a Tool for Monitoring and Managing the Technosphere Security of Uzbekistan - Muhammadiyeva Gulzoda Meliboy qizi; Zoyirjon Ibragimov; Rashidov Asilbek Furkat Ogli (Uzbekistan Open Conference, 2025)
In the modern world, ensuring technosphere safety has acquired special significance, especially in the context of rapid digitalization. One of the promising directions is the use of Internet of Things (IoT) technologies. In Uzbekistan, this direction is gradually being applied in monitoring industrial facilities, controlling environmental conditions, and managing engineering networks. IoT allows for real-time collection, analysis, and transmission of data on various parameters, which significantly improves decision-making efficiency and reduces the likelihood of emergency situations. Moreover, digital solutions open up opportunities for more rational use of resources and ensuring ecological sustainability. Thus, the implementation of IoT technologies is considered an important tool for enhancing technosphere safety and developing modern infrastructure in Uzbekistan.
Keywords: Internet of Things (IoT); technosphere safety; Uzbekistan; monitoring; management; digitalization; intelligent sensors; cybersecurity; engineering systems; sustainable development; automation; big data; innovative technologies; predictive analytics; digital infrastructure